ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PERAMPINGAN STRUKTUR PENGELOLA PADA STIE MUJAHIDIN TOLITOLI - Andhy Saputra; Ijma Ijma (Economy Deposit Journal (E-DJ), 2019)
Good governance of private tertiary institutions is a series of mechanisms to direct and control a tertiary institution so that it runs in accordance with the expectations of all interested parties, by applying the principles of transparency, accountability, responsibility, fairness, independence, equality and fairness. This study aims to determine and analyze the financial performance of STIE Mujahidin Tolitoli in terms of liquidity ratios, solvency ratios, activity ratios and profitability ratios. The study uses a quantitative research approach design by analyzing primary data. Based on the results of research and discussion it can be concluded that the financial performance condition of STIE Mujahidin Tolitoli in terms of Liquidity, Solvency, Activity and Profitability aspects after streamlining the manager structure has increased in value which can be interpreted that the financial performance after streamlining the manager structure is better than before because the value continues to increase and is above the industry average standard.